Incidences of Splenic Injury Associated with Blunt Truma to Left Lower Thoracic Ribs - Traim, Qasim; Jamel , Wameth Alaa; Hasin, Alaa Jamel (American Journal of Biomedicine and Pharmacy, 2025)
The spleen is the most frequently injured solid organ that occurs after blunt abdominal trauma, especially when the left lower part of the chest is the one that is hit. Spleen injury can lead to life threatening bleeding because of its location that is below the 9th11th ribs and its rich vascularity without immediate diagnosis and treatment. The purpose of this investigation was to determine the correlation between blunt trauma patients with fractures of the lower ribs of the left side and the splenic trauma. The proposed observational study was carried out in the emergency departments of Al-Nassiriya Teaching Hospital and Al-Hussein Teaching Hospital within 2 years, i.e., between 15 March 2021 to 14 February 2023. There were 96 patients who sustained blunt trauma of the left lower chest and /or abdomen. Diagnosis was performed in terms of clinical examination, chest radiography, abdominal ultrasonography, and computed tomography. In 74, splenic rupture was observed (77.08%). The density of splenic trauma by the severity of rib fractures showed that 59.4% of all splenic injuries were three-rib fractures (9th -11th). Single rib fractures constituted 12.1% of fractures, most often the 10 th rib. The majority of the patients had to undergo splenectomy (87.8). Splenic injury is highly predicted by left lower or multiple rib fractures. The morbidity and mortality should be minimized by early imaging and immediate management.